Society “Possessed by Ecology” is it a Threat to Human Freedom and Democracy? - Piątek, Zdzisława (Problemy Ekorozwoju, 2011)
The aim of this paper is a critical analysis of ecophilosophy and pro-ecologial politics. I present the arguments of the supporters of liberal capitalism on the basis of Vaclav Klaus’s opinions; and the arguments of traditional humanism on the basis of the views of Luc Ferry. My analysis will demonstrate that Klaus’s polemics with the supporters of the so called ‘environmentalism’ is based on a misunderstanding. Whereas Luc Ferry’s critical arguments fail to take into account the historical development of humanism. In conclusion I demonstrate that, contrary to what Ferry claims, pro-ecological politics does not involve a breach with the humanistic tradition, it only requires a reform of that tradition. In a new phase of development of humanism, which we may call the ‘humanism of tomorrow’, human improvement does not entail a breach with Nature, or a conquest of Nature, it entails a new pact with Nature that will be realized by means of sustainable development.